Search for charged Higgs bosons in the H± → τ±ντ decay channel in proton-proton collisions at √s=13 TeV; Journal of High Energy Physics; Vol. 2019, iss. 7 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen